The Influence of Transformational Leadership Style, Organizational Commitment, Reward and Punishment on Performance-Based Budgeting: Empirical Study at Public Broadcasting Institutions in Jambi City - Putri, Yumiza Aprilia; Hizazi, Achmad; Gowon, Muhammad (International Journal of Multidisciplinary Approach Research and Science, 2024)
This research aims to analyze and prove empirically the influence of transformational leadership style, organizational commitment, rewards and punishment on performance-based budgeting at public broadcasting institutions in Jambi City. This research used a purposive sampling method with 37 respondents in this study. Data collection was carried out using a questionnaire. The data analysis method uses validity and reliability tests, classical assumption tests and hypothesis testing using multiple linear regression with the help of the SPSS version 29 software program. The research results show that partially Transformational Leadership Style and Organizational Commitment have an effect on Performance-Based Budgeting, while Reward and Punishment do not influence on Performance Based Budgeting. Simultaneously Transformational Leadership Style, Organizational Commitment, Reward and Punishment influence Performance-Based Budgeting at Public Broadcasting Institutions in Jambi City.